Estudio de un plan de organización de materia prima e insumos en el área de bodega para agilitar los procesos productivos en la Empresa Industrial Metálica Cotopaxi. - Velasco Quimbita, Wilma Jeaneth (2018)
The study plan the organization of raw materials and inputs in the warehouse area of the company Industrial Metálica Cotopaxi, where the process of transfer and transportation of the raw material and inputs determined and recording the times, to the different stations is analyzed of work from the collection of the material to the cutting areas, ovens, stoves, mixers and doors. Identifying that in the request for supplies of the winery more time is spent in the stages of concinas and ovens. The personnel that works in these areas of work does not know very well about the activities as it was possible to identify when carrying out a previous survey, for the lifting of the time it was done with the method by timing, with which the time of each work area, obtaining a total of 1.54 hours of employee time. For the reduction of times and movements, a training was proposed for the warehouse personnel of the company regarding the handling of raw materials and supplies and to improve the distribution of the warehouse, through the training carried out, the times in the application were reduced of materials orders, this allows the industry to improve its manufacturing processes and optimize times when it used to take longer. The company must establish a constant training program for the personnel of the production area that allows them to use the best form of the resources.